Gra z romantycznym afektem w Mariaszu Artura Daniela Liskowackiego - Malicka, Patrycja (Przestrzenie Teorii, 2017)
The aim of the article is to show the connection between affection theory and romantic concepts of emotions (mesmerism and melancholy) in Artur Daniel Liskowacki’s 2007 novel Mariasz. By way of introduction, the author presents in brief the most important research on affective turn conducted in Poland and around the world, and also shows the possibilities of affective reading. The next part of the article is an interpretation of Mariasz. What is more, affection theory, as it is used in the novel, helps us to describe the ambiguous network of relations between the characters more fully and clearly, who experience similar affections, despite the temporal distance between them (romanticism and modernity). By analyzing Liskowacki’s novel we can identify the current relevance of the Romantic tradition in Polish literature after 1989, which is far from its martyrological connotations. Romanticism becomes a reference point for contemporary times, and original dialogues from that epoch allow the emotional nature of humans immersed in contemporary times to be described in full.